Hoc primum condita Roma loco est (Ov. Tr. III 1,32) - Roma quadrata w propagandzie Augusta - Zawadzka, Anna (Instytut Studiów Klasycznych, Śródziemnomorskich i Orientalnych Uniwersytetu Wrocławskiego, 2012)
The article is devoted to the term ‘Roma quadrata’ in connection with the beginnings of Rome.The oldest messages which present Roma Quadrata as a place originate from the Augustan period and are steeped in Augustan propaganda.
Keywords: Roma quadrata; origin of Rome; Ovid; Verrius Flaccus; Augustus; propaganda